2021
DOI: 10.1002/bem.22350
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Level Radiofrequency Exposure Induces Vasoconstriction in Rats

Abstract: Recent studies have revealed that rodents' physiological responses to low intensity radiofrequency electromagnetic fields (RF) were similar to thermoregulatory responses to cold conditions. The primary autonomic response to cold exposure is peripheral vasoconstriction that allows rodents to reduce heat loss and maintain a relatively constant internal body temperature. In the present study, we investigated the effects of 900 MHz RF at a low level (SAR of 0.35 W.kg -1 ) on tail skin temperature (T tail ) in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…When exposed to a cold stimulus, the cold-sensitive neurons located in the POA and the activation of the HPA axis induce the secretion of catecholamines (epinephrine and NE) and other neurotransmitters such as neuropeptide and ATP [ 35 ]. Consequently, they activate receptors in the blood vessels to produce vasoconstriction [ 125 , 126 ] to divert blood flow from the limbs or peripheral structures to vital organs [ 127 , 128 , 129 ]. Solomon et al [ 130 ] demonstrated this in four Long Evans rats ( Rattus norvegicus ) subjected to motility frustration (e.g., not being able to use an activity wheel).…”
Section: Thermoregulatory Mechanisms In Altricial and Precocial Speciesmentioning
confidence: 99%
“…When exposed to a cold stimulus, the cold-sensitive neurons located in the POA and the activation of the HPA axis induce the secretion of catecholamines (epinephrine and NE) and other neurotransmitters such as neuropeptide and ATP [ 35 ]. Consequently, they activate receptors in the blood vessels to produce vasoconstriction [ 125 , 126 ] to divert blood flow from the limbs or peripheral structures to vital organs [ 127 , 128 , 129 ]. Solomon et al [ 130 ] demonstrated this in four Long Evans rats ( Rattus norvegicus ) subjected to motility frustration (e.g., not being able to use an activity wheel).…”
Section: Thermoregulatory Mechanisms In Altricial and Precocial Speciesmentioning
confidence: 99%
“…In the case of cold stimuli, the participation of the HPA axis, the secretion of catecholamines (epinephrine and norepinephrine), and their action on the receptors located in the blood vessels generate a vasoconstriction effect [122,123]. The objective of vasoconstriction is to redirect the blood flow of the extremities or peripheral structures toward internal organs and vital centers, limiting heat loss through the skin [124][125][126].…”
Section: Vasomotor Controlmentioning
confidence: 99%